Evaluate the argon plasma jet parameters by optical emission spectroscopy - Harakat Mohsin Roomy; N. Yasoob A.; Hamid H. Murbat (Kuwait Journal of Science)
In this study, a method for experimentally evaluating the plasma parameters in the Argon plasma jet system with varying rates of Argon gas flow from 1 to 5 ​L/min operating at constant voltage and normal atmospheric pressure. This study is based on optical emission spectroscopy (OES). Spectroscopic diagnostic method using the Boltzmann plot to calculate these parameters measured. Generally, the results show the value of Te ranged from 1.53 to 1.78 (eV) depending on the gas flow rates, electron density ranges from 2.63 to 3.12 ​× ​1017 (cm−3). The plasma parameters such as (λD, ND, and ωp) related to electron temperature and electron density was also measured. The plasma was produced at a different flow rate the impacts on Debye length, plasma frequency, and the number of particles on the surface of Debye, all of which rise with an increase in gas flow rate, are significantly influenced by an increase in gas flow rate on the plasma properties of the density and temperature of an electron.